About Stefan Scharfenberg's way of reading Paul Ricœurs's "Time and narration" (KULT_online, 2013)
The work “Time and narration” of the French hermeneutics scholar Paul Ricœur has scarcely been recognized in Germany. Taking into consideration its limited status of acceptance a critical analysis of Ricœur's theory is extremely welcome, especially because this analysis is dedicated to one of the least considered parts – the concept of the narrative identity. The author's main purpose is to raise the concept of the narrative identity which only appears in the conclusions of the third volume, “to a systematic leading concept of an analysis of time and narration” (page 18). There is no doubt that such a leading concept is needed, given the substantial intellectual and conceptual broadness of time and narration. In view of the approach of the author it seems to be questionable whether such concept of the narrative identity is stable for this; it requires detailed Prolegomena of more than 250 pages before the notion of the narrative identity is directly used. Nevertheless the analysis can be recommended as a valuable and critical comment for all who are interested in it.